Fast assessment and management of chest pain patients without ST-elevation in the pre-hospital gateway (FamouS Triage): ruling out a myocardial infarction at home with the modified HEART score. Issue 2 (March 2018) - Ishak, Maycel; Ali, Danish; Fokkert, Marion J; Slingerland, Robbert J; Tolsma, Rudolf T; Badings, Erik; van der Sluis, Aize; van Eenennaam, Fred; Mosterd, Arend; ten Berg, Jurriën M; van 't Hof, Arnoud WJ
Background: The first study of the FamouS Triage project investigates the feasibility of ruling out a myocardial infarction in pre-hospital chest pain patients without electrocardiographic ST-segment elevation by using the modified HEART score at the patient's home, incorporating only a single highly sensitive troponin T measurement. Methods: A venous blood sample was drawn in the ambulance from 1127 consecutive chest pain patients for measurement of the pre-hospital highly sensitive troponin T levels, in order to establish a pre-hospital HEART score (i.e. the modified HEART score) and evaluate the possibility of triage at the patient's home. The primary endpoint was the occurrence of a major adverse cardiac event (MACE) i.e. acute myocardial infarction, percutaneous coronary intervention, coronary artery bypass grafting or death within 30 days after initial presentation. Results: Two hundred and six patients (18%) developed a MACE during 30 days of follow-up. Thirty-six per cent of the patients ( n =403) had a low modified HEART score (0–3 points) and none of them developed a MACE during follow-up. Forty-four per cent of the patients ( n =494) had an intermediate modified HEART score (4–6 points) and 18% of them developed a MACE. Twenty per cent of the patients ( n =230) had a high modified HEART score (7–10 points) of which 52% developed a MACE during follow-up. Conclusion: It seems feasible to rule out a myocardial infarction at home in chest pain patients without ST-segment elevation by using the modified HEART score. TRIAL ID: NTR4205. Dutch Trial Register [http://www.trialregister.nl ]: trial number 4205.